Coupled heat and mass transfer simulation of CRUD migration and deposition in PWR systems - Xuesong Li; Meng Zhang; Yang Gao; Hongguo Hou; Caishan Jiao; Nan Chao (Nuclear Engineering and Technology)
In Pressurized Water Reactors (PWRs), corrosion products are released during operation due to the large contact area between the primary circuit coolant and the equipment materials. In this study, a multiphysics model was developed and validated to simulate and analyze the migration and deposition behavior of corrosion products in the primary circuit. The model is useful for calculating the effect of operating conditions on migration and deposition. The effects of mass transfer and subcooled boiling on deposition and re-release were included in the model. Diffusion, convective mass transfer, and transition between ions and particles in the coolant were also considered in the model.The model's accuracy was validated by comparison with actual measured data from the Callaway reactor. Calculations showed that the deposition on the steam generator exceeded that on other equipment, primarily attributable to its larger surface area. Additionally, variations in the coolant flow significantly influence the deposition resulting from subcooled boiling, with an increase in flow leading to a noticeable reduction in boiling deposition.